Role of PI3K in the bone resorption of apical periodontitis - LiNa Wang; Ming Dong; DongMei Shi; CaiHui Yang; Shuo Liu; Lu Gao; WeiDong Niu (BMC, 2022)
Abstract Background Phosphoinositide 3-kinase (PI3K) is located within cells, and is involved in regulating cell survival, proliferation, apoptosis and angiogenesis. The purpose of this study was to investigate the role of PI3K in the process of bone destruction in apical periodontitis, and provide reference data for the treatment of this disease. Methods The relative mRNA expression of PI3K, Acp5 and NFATc1 in the normal human periodontal ligament and in chronic apical periodontitis were analyzed by real-time quantitative polymerase chain reaction (RT-qPCR). A mouse model of apical periodontitis was established by root canal exposure to the oral cavity, and HE staining was used to observe the progress of apical periodontitis. Immunohistochemical staining was used to detect the expression of PI3K and AKT in different stages of apical periodontitis, while enzymatic histochemical staining was used for detection of osteoclasts. An Escherichia coli lipopolysaccharide (LPS)-mediated inflammatory environment was also established at the osteoclast and osteoblast level, and osteoclasts or osteoblasts were treated with the PI3K inhibitor LY294002 to examine the role of PI3K in bone resorption. Results The expression of PI3K, Acp5 and NFATc1 genes in chronic apical periodontitis sample groups was significantly increased relative to healthy periodontal ligament tissue (P < 0.05). Mouse apical periodontitis was successfully established and bone resorption peaked between 2 and 3 weeks (P < 0.05). The expression of PI3K and Akt increased with the progression of inflammation, and reached a peak at 14 days (P < 0.05). The gene and protein expression of PI3K, TRAP and NFATc1 in osteoclasts were significantly increased (P < 0.05) in the E. coli LPS-mediated inflammatory microenvironment compared to the normal control group. Meanwhile in osteoblasts, the gene and protein expression of PI3K, BMP-2 and Runx2 were significantly reduced (P < 0.05) in the inflammatory microenvironment. With the addition of LY294002, expressions of bone resorption-related factors (TRAP, NFATc1) and bone formation-related factors (BMP-2, Runx2) significantly decreased (P < 0.05). Conclusions Under the inflammatory environment induced by LPS, PI3K participates in the occurrence and development of chronic apical periodontitis by regulating the proliferation and differentiation of osteoclasts and osteoblasts.